Power Concavity for Doubly Nonlinear Parabolic Equations (Journal of Mathematical Study, 2017)
We prove the concavity of the power of a solution is preserved for a class ofdoubly nonlinear parabolic equation, which is a well-known feature in some particularcases such as the porous medium equation or the parabolic $p$-Laplace equation.